Analysis of Internal Risk Management in Indonesian Seaweed Farming - Thahir, Harifuddin; Rombe, Elimawaty; ., Ponisri; Vesakha, Gatha; Hadi, Suryadi (International Journal of Engineering and Technology, 2018)
This study aims to identify the internal risk management and acknowledge the highest and the lowest risk that have significant impact on seaweed farming in Indonesia. The case study is used in Morowali-the central seaweed farming in Indonesia. The data obtained from primary data and secondary data and used a census through interview and questionnaire. Data analysis apply analytic hierarchy process (AHP) to determine the weight of each criterion and sub criteria. The results show that the internal risks of seaweed operation by Indonesian farmers include the quality of seeds, technology, human resources, capital and cost management. The study found that the highest internal risk of seaweed operation on the farmers level is technology. This study provides insight and information to the seaweed farmers and manager of seaweed industry about the typical of internal risks in the farmers level.